Topics of Interest to Women in Educational Administration - Marilyn L. Grady; Doreen Gosmire (Educational Considerations, 1995)
The topical Interests [training needs] of women in K-12 and post secondary administration were quite similar. Those interested in providing professional development opportunities should be attentive to the fourteen areas of training needs indicated by the respondents [in this study].